Perbedaan Efektivitas Ekstrak Hiji Pala (Myristica Fragnas Houtt) Dengan DIazepam Berdasarkan Durasi Tidur Mencit Swiss Webster - Bella Ayu Aprilya; Deby Mirani Lubis (Universitas Muhammadiyah Sumatera Utara, 2020)
Abstract: According to National Sleep Foundation in America, more than onethird (36%) in young adults aged 18-29 years old reported hard to wake up in themorning. Nutmeg seeds contain atsiri oil about 10% and miristin that havesedative effect. The purpose of this study is to prove that nutmeg seeds shortensleep induction time and prolong sleep time. This type of research is experimentalresearch with a post test only control group design. The samples used were 27male Swiss Webster mice, which were divided into three groups. The first controlgroup was given diazepam; the second group was given nutmeg seed extract doseof 7.5 mg; and the third group was given aquabides. The data obtained from thesleep duration of mice in each group. To determine differences in eachexperimental group, data with normal distribution were analyzed by one wayANOVA test and data with abnormal distribution were analyzed by the KruskalWallistest using SPSS 22.0 for Windows. The results of the Kruskal-Wallis testshowed that sleep induction time had a value of p = 0.001. Based on the one wayANOVA test, the result shows the length of sleep time from the treatment grouphas a significant difference to the control group with a value of p = 0,000 andalso showing a significant result to the comparison group with a value of p =0,000. Nutmeg seed extract (Myristica fragrans Houtt.) with a dose of 7.5 mg cansignificantly extend the sleep duration of mice. Keywords: nutmeg seeds extract, sleep duration.